Rechazo activo de perturbaciones en vehículos aéreos multirotor. - Alvarez Liceaga, Ulises (2018)
Objetivos y metodo de estudio: ´ The general objective of this thesis is to create and test a control for multirotor aircraft that is resistant to disturbances. Contribuciones y conlusiones: The proposed controller has the ability to be implemented into any type of multirotor vehicle.